2022
DOI: 10.1111/gcbb.12985
|View full text |Cite
|
Sign up to set email alerts
|

Site impacts nutrient translocation efficiency in intraspecies and interspecies miscanthus hybrids on marginal lands

Abstract: Miscanthus, a C4 perennial rhizomatous grass, is capable of growing in varied climates and soil types in Europe, including on marginal lands. It can produce high yields with low nutrient inputs when harvested after complete senescence. Senescence induction and rate depend on complex genetic, environmental, and management interactions. To explore these interactions, we analysed four miscanthus hybrids (two novel seed‐based hybrids, GRC 3 [Miscanthus sinensis × sinensis] and GRC 14 [M. sacchariflorus × sinensis]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…For climates with mild wet winters where the more productive sac × sin hybrids are grown harvest methods are being developed to reduce the moisture before the crop is transported from the field, such as the common technique in wetter climates of cutting to a swath (Hastings et al, 2017; Lewandowski et al, 2000). This moisture content is very affected by leaf to stem ratio at harvest, with leaf contributing more moisture (Magenau, Clifton‐Brown, Awty‐Carroll, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For climates with mild wet winters where the more productive sac × sin hybrids are grown harvest methods are being developed to reduce the moisture before the crop is transported from the field, such as the common technique in wetter climates of cutting to a swath (Hastings et al, 2017; Lewandowski et al, 2000). This moisture content is very affected by leaf to stem ratio at harvest, with leaf contributing more moisture (Magenau, Clifton‐Brown, Awty‐Carroll, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We found that M sin × sin (GRC 3) has a more effective strategy for avoiding damage from late spring frosts: firstly, later emergence and secondly, higher frost tolerance. This could help explain why M sin × sin achieves higher yields than M × g and M sac×sin at colder locations (Awty‐Carroll et al, 2022; Magenau et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…The end-of-season ripening behaviour of miscanthus is a main driver for maintaining a high harvestable yield quantity, while achieving biomass quality requirements and minimizing nutrient offtakes by the harvested biomass. Magenau et al (2022) studied the dynamics of the senescence processes of different miscanthus hybrids. Generally, it was found that delaying the harvest until spring reduced overall yield, moisture and nutrient contents for all novel hybrids tested.…”
Section: Section 2: Industrial Crop Cultivationmentioning
confidence: 99%
“…Magenau et al. (2022) studied the dynamics of the senescence processes of different miscanthus hybrids. Generally, it was found that delaying the harvest until spring reduced overall yield, moisture and nutrient contents for all novel hybrids tested.…”
Section: Section 2: Industrial Crop Cultivationmentioning
confidence: 99%